Pasir Panjang Beach Tourist Area with an Eco Resort Architectural Approach - Ainul, Ainul; Nahdatunnisa, Nahdatunnisa; Abidin, Afri Ahyarky (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The rapid development of tourism in Morowali Regency has made me raise one of the tourist attractions in Morowali Regency, namely the Pasir Panjang Beach tourism which has a tourist attraction whose beautiful beach is still very well preserved. This tourist area is located in Pu'ungkeu Village, Bungku Pesisir District, Morowali Regency, Central Sulawesi, which is not far from residential areas. The purpose of this planning is to design a suitable site so that it can accommodate tourist activities in the tourist area, to plan facilities and infrastructure that can accommodate tourism activities, to apply the principles of eco resort architectural design in designing areas and buildings in the Pasir Panjang beach tourist area. The research method used is Descriptive Qualitative with an approach in the form of primary data, namely conducting direct observations at the research location, secondary data, namely data obtained from libraries in the form of textbooks, journals, documentation, research institution data, and agency data, as well as data collection techniques which then analyze the data. The results of the study indicate that the Pasir Panjang Beach Tourism Area needs to be reviewed in developing supporting facilities for visitors to meet the needs and comfort of traveling, using the principles of eco resort architectural design where the architectural design applies a design in the form of a building that has a reciprocal relationship with nature. so that it can produce a design that provides a prosperous living environment by presenting nature into the building.